Perceptions of the impact of military life on relationships and Intimate Partner Violence and Abuse among UK military personnel - Rebecca Lane; Filipa Alves-Costa; Rachael Gribble; Anna Taylor; Louise M. Howard; Nicola T. Fear; Deirdre MacManus (PLoS ONE, 2025)
Research suggests that the prevalence of Intimate Partner Violence and Abuse (IPVA) use (i.e., perpetration) and experience (i.e., victimisation) is higher among military compared to civilian populations and that military-related factors, such as deployment and deployment-related trauma, are associated with IPVA. However, the mechanisms underlying the associations between military factors and IPVA use and experience are not well understood. This study explores narratives of how military personnel perceive military life to influence IPVA within relationships. Semi-structured interviews were conducted with 40 UK military serving and ex-serving personnel (29 male, 11 female) and analysed using Framework analysis. Three superordinate themes were derived describing how elements of military life were perceived by personnel and veterans to impact on relationships and contribute to IPVA: Demands of military work; Military cultural spill-over; and Deployment-related difficulties with psychosocial functioning and mental health. The findings highlight risky periods for relationship conflict and IPVA, especially during reintegrations following deployments, but also show the impact of other military factors which provide significant context for IPVA. Our findings emphasise how difficulties with psychosocial functioning and communication, as well as deployment-related traumas and reintegration challenges, can influence relationships and IPVA behaviours among military personnel and veterans. Such experiences are aggravated or perpetuated by occupational demands, military socialization or institutionalisation, and the hypermasculine military environment. Targeted interventions to improve emotion regulation, conflict resolution and mentalizing skills may be especially useful for minimising harm resulting from relationship conflict and preventing IPVA.